Graphene oxide supported sulfidated nano zero-valent iron (S-nZVI@GO) for antimony removal: The role of active oxygen species and reaction mechanism. (December 2022) - Chi, Zifang; Ju, Shijie; Liu, Xinyang; Sun, Feiyang; Zhu, Yuhuan
Abstract: Sulfidated nano zero-valent iron (S-nZVI) was used to remove various pollutants from wastewater. However, the instability, poor dispersibility, and low electron transfer efficiency of S-nZVI limit its application. Herein, graphene oxide supported sulfidated nano zero-valent iron (S-nZVI@GO) was successfully synthesized using graphene oxide (GO) as a carrier. The properties of S-nZVI@GO were characterized by scanning electron microscopy coupled to X-ray photoelectron spectroscopy (SEM-EDS), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) concerning the surface morphology, crystalline structure, and elemental components. S-nZVI@GO displayed an excellent capacity for antimony (Sb) removal under aerobic conditions (96.7%), with a high adsorption capacity (Qmax  = 311.75 mg/g). It maintained a high removal rate (over 90%) during a wide pH range (3–9). More importantly, S-nZVI@GO activated the molecular oxygen in water via a single-electron pathway to produce O2 － and H2 O2, and then oxidized trivalent antimony (Sb(III)) to pentavalent antimony (Sb(V)) and further separated it by synergistic adsorption and co-precipitation. Therefore, S-nZVI@GO shows excellent potential for Sb contamination remediation. Graphical abstract: Image 1 Highlights: S-nZVI@GO displayed good capacity for antimony removal under aerobic conditions. High antimony removal was maintained over a wide range of pH. S-nZVI@GO activated molecular oxygen via a single electron pathway. O2 − and H2 O2 were important active oxygen species Antimony removal was related to oxidation-adsorption-co-precipitation.